Perintisan Pelayanan Kelompok Sel di Gereja Bandung City Blessing Petra - Ferry Simanjuntak; Ana Ariesanita; Hana Venturini; Ernavina Pelmelay; Hana Yolanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2022)
Abstract Church planting cannot be separated from mission, because a church can be said to develop and grow if the church carries out a mission. Church activities that were hampered because of the pandemic did not hinder the spirit of God's church as the